Analisis Biaya Relevan Dalam Menentukan Pengambilan Keputusan Menerima Atau Menolak Pesanan Khusus Pada UD. Sejati Mulia - Sutarti, Sutarti (Jurnal Ilmiah Kesatuan (JIK), 2010)
The background serves as a basis for this research is relevant cost information to make decision to accept or reject special order. Relevant cost is future cost that affect decision to make of. Relevant cost information in decision making on special order is based on cost behaviour analysis. The object of this research is UD Sejati Mulia in Surabaya which has not applied relevant cost analysis method yet to make decision to accept or reject special order. UD is an Indonesia abbreviation which mean Trading of Commerce. The information used is the costs in the years 2004 â 2008. The cost behaviour analysis is used to classify costs to be fixed cost, semivariable cost, and variable cost. The separation of semivariable into fixed element and variable element uses least square method. The approach used in this reseach is descriptive approach which illustrate the situation of the corporation itself compared to external environment. Data are gotten by means of interview, documentation study, and observation. The relevant cost analysis used to separate variable cost, fixed cost, and semivariable cost is relevant to make decision either to accept or to reject special order because not all costs can be categorized as relevant cost. The decision to accept or to reject special order will be better to pay attention to external factors as well such as marketing area of special order should be different from regular order. In addition, the effect of brand given by distributor should be taken note of as well. The result of this reseach shows that if the corporation accepts special order, it earns additional profit as high as Rp8.805.573,70 for rice flour special order and Rp4.030.764, 93 for cooking spices special order in addition to take an advantage of idle capacity.